VARIASI BAHASA CAMPUR KODE DAN BAHASA GAUL (SLANG) DALAM PLATFORM MEDIA SOSIAL X - Fairuz, Fathiya; Kundharu Saddhono (Universitas Terbuka, 2024)
Languages has various types, and they are always evolving with the times. Foreign languages are the second or companion languages of the main language, from this foreign language there is often a mixing of codes in Indonesian. Then, slang is a modification of the language that already exists in society. This study aims to analyze the use of mixed code and slang on social media, especially in the comments of @kegblgunfaedh accounts on platform X. The method used is qualitative descriptive to uncover this phenomenon. The results of the study show that social media users often use slang and mixed code. Slang is used to create familiarity, while code mix arises spontaneously due to environmental influences. This study concludes that language variations in social media reflect the dynamics and development of language in society.